Nitrous oxide emission factors for urine and dung from sheep fed either fresh forage rape (Brassica napus L.) or fresh perennial ryegrass (Lolium perenne L.). (19th November 2014) - Luo, J.; Sun, X. Z.; Pacheco, D.; Ledgard, S. F.; Lindsey, S. B.; Hoogendoorn, C. J.; Wise, B.; Watkins, N. L.
Abstract : In New Zealand, agriculture is predominantly based on pastoral grazing systems and animal excreta deposited on soil during grazing have been identified as a major source of nitrous oxide (N2 O) emissions. Forage brassicas ( Brassica spp.) have been increasingly used to improve lamb performance. Compared with conventional forage perennial ryegrass ( Lolium perenne L.), a common forage in New Zealand, forage brassicas have faster growth rates, higher dry matter production and higher nutritive value. The aim of this study was to determine the partitioning of dietary nitrogen (N) between urine and dung in the excreta from sheep fed forage brassica rape ( B . napus subsp. oleifera L.) or ryegrass, and then to measure N2 O emissions when the excreta from the two different feed sources were applied to a pasture soil. A sheep metabolism study was conducted to determine urine and dung-N outputs from sheep fed forage rape or ryegrass, and N partitioning between urine and dung. Urine and dung were collected and then used in a field plot experiment for measuring N2 O emissions. The experimental site contained a perennial ryegrass/white clover pasture on a poorly drained silt-loam soil. The treatments included urine from sheep fed forage rape or ryegrass, dung from sheep fed forage rape or ryegrass, and a control without dung or urine applied. N2 O emission measurements were carried out using a static chamber technique. For each excreta type, the total N2 O emissions and emission factor (EF3; N2 O–N emitted during the 3- or 8-month measurement period as a per cent of animal urine or dung-N applied, respectively) were calculated. Our results indicate that, in terms of per unit of N intake, a similar amount of N was excreted in urine from sheep fed either forage rape or ryegrass, but less dung N was excreted from sheep fed forage rape than ryegrass. The EF3 for urine from sheep fed forage rape was lower compared with urine from sheep fed ryegrass. This may have been because of plant secondary metabolites, such as glucosinolates in forage rape and their degradation products, are transferred to urine and affect soil N transformation processes. However, the difference in the EF3 for dung from sheep fed ryegrass and forage rape was not significant.